The development of smart screening technology kit (SST-Kit) for sorting cassava cultivars based on cyanide analysis - Luluil Maknun; Noerma Juli Azhari; Mike Nur Izzati; Rizal Nur Huda; Abdul Malik Bahrudin; Erliana Ginting; Hermin Sulistyarti (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
Cyanides are deadly toxic substances commonly found in cassava root tuber. Higher content of cyanides causes bitter taste of the root tuber. Therefore, analysis of cyanide content has been used as one of criteria for bitterness in cassava. The substitute common method used for this purpose was organoleptic test that could lead to poisoning, or argentometry, which is complicated, time-consuming, and requires lots of reagents. Therefore, a fast, easy, and safe method is strongly demanded. In this work, a smart screening technology kit (SST-Kit) was developed using ninhydrin reagent. This simple, fast, and low-cost method can be applied in the field for the analysis of cyanide levels in cassava. This method was optimized to the concentration of sodium carbonate from 0.5 to 2.0% by measuring the red color intensity produced under various times of reading from 1 to 3 minutes and three sample preparation techniques. The optimum condition for SST-Kit to read the cyanides level was achieved under the condition of 0.5% of sodium carbonate with a time readout of 2 minutes, using grinding preparation technique followed by dilution. The SST-kit had been applied on cassava samples with the accuracy of more than 90%.